Tools for technology management an academic perspective - Brady, T.; Rush, H.; Hobday, M.; Davies, A.; Probert, D.; Banerjee, S.
The value of management tools is occasionally brought into question. They are sometimes seen as some form of crutch which managers deploy instead of thinking creatively. This paper attempts to clarify the nature of management tools and argues a case for their appropriate use. The paper distinguishes between tools and company procedures or systems and explores some new categorisations. Focusing specifically on technology management tools, the paper looks at where different tools have come from, and provides examples from industry, government and consultancy companies. The role academics can play in their development is explored, with the paper arguing that they are in a rare position to impartially scrutinise and evaluate existing tools as well as contribute to the development of new tools to solve unusual and complex problems.
Technology management requires new and improved tools to assist in the development of products : the paper examines existing tools of management and suggests areas where academics may provide new tools, such as complex problem solving.
Keywords: Technology management